Isolation and cloning of the Sordaria macrospora ura3 gene and its heterologous expression in Aspergillus niger - M Nowrousian; U KUCK (Fungal Genetics Reports, 1998)
We report the isolation and molecular characterization of the ura3 gene encoding orotidine monophosphate decarboxylase (OMPD) from Sordaria macrospora. Pulsed field gel electrophoresis and Southern hybridization revealed that the ura3 gene is located on chromosomes VI / VII of S. macrospora. A functional analysis of the S. macrospora ura3 gene was performed by DNA transformation using an Aspergillus niger pyrA mutant as recipient strain.